Characteristics of implicit schemas in patients with major depressive disorder. Issue 3 (28th June 2022) - Yao, Jiayu; Lin, Qingqing; Zheng, Ziwei; Chen, Shuangyi; Wang, Yuan; Jiang, Wenhui; Qiu, Jianyin
Abstract : Background: Many psychotherapy theories emphasise the importance of self-schema and other-schema, but most previous studies focused on the explicit self-schema in major depressive disorder (MDD). However, the limited studies of implicit self-schema in MDD have shown inconsistencies in their findings. Furthermore, only a few studies have investigated the implicit other-schema, and the pathway illustrating how implicit schemas influence depression remains unclear. Aims: The primary aim of our study was to explore the characteristics of implicit self-schema and other-schema in patients with MDD. We also examine the chain-mediating effect of attachment relationships and interpersonal trust. Methods: The present study included 88 patients with MDD and 88 healthy controls (HCs). The Hamilton Depression Rating Scale-17, Experiences in Close Relationships Inventory—Revised Questionnaire, Trust Scale and the Extrinsic Affective Simon Task (EAST) were used to assess depressive symptoms, attachment relationships, interpersonal trust and implicit schemas, respectively. Paired sample t-test was used to compare the reaction time (RT) for positive and negative words within the two groups. Analysis of covariance was used to explore the difference between two groups from the perspective of implicit schemas and interpersonal patterns. The chain mediation model was verified by bootstrap. Results: (1) For interpersonal patterns, patients with MDD scored significantly higher on attachment anxiety (F=82.150, p<0.001) and attachment avoidance (F=23.192, p<0.001) and scored significantly lower on the predictability (F=30.297, p<0.001), dependence (F=39.728, p<0.001) and faith (F=60.997, p<0.001) dimensions of interpersonal trust. (2) As for implicit schemas, no significant difference was found between the RT for positive self-words and negative self-words in patients with MDD (t=−1.056, p=0.294). However, the HC responded faster to positive self-words than negative self-words (t=−3.286, p=0.001). The RT for positive other-words and negative other-words were significantly different in both patients with MDD (t=2.943, p=0.004) and HCs (t=−2.482, p=0.015), with opposite directions. The EAST effect of other-schema in patients with MDD was significantly different from that in HCs (F=13.051, p<0.001). (3) For the total sample, the EAST effect of other-schema significantly correlated with attachment avoidance, interpersonal trust and depressive symptoms. Attachment avoidance and interpersonal trust were the chain mediators between the EAST effect of other-schema and depressive symptoms (95% CI: −0.090 to −0.008). However, no significant results were found for the EAST effect of other-schema when correlation and mediation analyses were performed for HCs and patients with MDD separately. Conclusions: This study verified that patients with MDD have abnormal interpersonal patterns and negative implicit schemas. However, no mediating effect of attachment relationships and interpersonal trust was found.